Utilization of Partially Purified Papain Enzyme in Mallika Black Soybean Tempeh Hydrolysate as Umami Seasoning - Wihan, Leonardo Aditya; Anugrahati, Nuri Arum (Caraka Tani: Journal of Sustainable Agriculture, 2023)
Tempeh made from Mallika black soybean (Glycine max (L.) Merr. var. Mallika) can be fermented for up to 4 days and can be further optimized by adding partially purified papain enzyme obtained from California variety papaya leaves (Carica papaya (L.) var. California). Enzyme can be added to the hydrolysates to degrade protein into short-chain peptides and free amino acids, contributing to umami taste sensory attributes. The study aimed to determine the best ammonium sulfate fractionation of crude papain enzyme and the best physicochemical characteristics of black soybean tempeh protein hydrolysate. The addition of ammonium sulfate fractionation used was 0% to 80%; fermentation time was 2 to 4 days; and the concentration of enzyme added was 0%(w/v) to 1.5%(w/v). The results showed that the 40% fractioned papain enzyme gave the highest protease activity value (0.98±0.04 U ml-1) and most of the papain enzyme was precipitated in this fraction leaving impurities. The black soybean tempeh hydrolysates with 4 × 1% showed the best physicochemical characteristic because it produced the highest umami substance. The best characteristics were moisture content (17.97±0.46%), glutamic acid content (171.58±5.72 mg g-1) that was caused by a transamination reaction, dissolved protein content (470.66±19.50 mg g-1), degree of hydrolysis (43.64±1.99%) and lightness (46.02±0.97). The umami substance’s amino acids are high in content, such as glutamic and aspartic acids (59.89±0.31 mg g-1 and 26.47±0.09 mg g-1). Sensory evaluation showed that treatment 4 × 1% demonstrated no significant difference in umami intensity with MSG (monosodium glutamate).